2020
DOI: 10.3390/met10070857
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sample-Size on the Compression Deformation Behavior of a CuZr-Based Bulk Metallic Glass Composite

Abstract: The compressive deformation behaviors and microstructures of Cu45Zr48Al4Nb3 bulk metallic glass composites with diameters of 3, 2, and 1 mm were investigated systematically. It was found that the smallest sample showed the highest yield strength and compressive plasticity. The yield strength of the samples was found to depend on the fraction of their crystalline phases in the glassy matrix. The smaller samples showed larger free volumes, which is favorable for plastic deformation. The deformation behavior of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This further implies that if one can prepare a glass with structures that resemble more the interfacial regions, the β-relaxation and the capability of plastic deformation might be even more promoted. It has been demonstrated that the disordering of the microstructure and the rearrangement of atomic clusters can lead to an increase in plasticity in rejuvenated MGs. , Therefore, the interfacial regions with loosely arranged atoms in the nanoglass may also provide a structural basis for the improvement of its plasticity. Moreover, the interfacial regions also provide rooms for the elongation and rotation of the nanograins during deformation, rendering the materials more tolerant for deformation. , However, these interfacial regions may also cause unstable plasticity strains of the nanoglass during deformation .…”
mentioning
confidence: 99%
“…This further implies that if one can prepare a glass with structures that resemble more the interfacial regions, the β-relaxation and the capability of plastic deformation might be even more promoted. It has been demonstrated that the disordering of the microstructure and the rearrangement of atomic clusters can lead to an increase in plasticity in rejuvenated MGs. , Therefore, the interfacial regions with loosely arranged atoms in the nanoglass may also provide a structural basis for the improvement of its plasticity. Moreover, the interfacial regions also provide rooms for the elongation and rotation of the nanograins during deformation, rendering the materials more tolerant for deformation. , However, these interfacial regions may also cause unstable plasticity strains of the nanoglass during deformation .…”
mentioning
confidence: 99%
“…It was shown recently that the elastic modulus and hardness of a CuZrAl BMG synthesized by selective laser melting can be significantly improved [29]. The compression deformation behaviors of the ZrCu-based BMG samples was found to be size-dependent, i.e., the smallest sample exhibits the highest yield strength and compressive plasticity due to the larger free volume [30].…”
Section: Introductionmentioning
confidence: 98%